Halal all that you need to know (vol 1) - Hashim, Yumi Zuhanis Has-Yun (Institut Terjemahan & Buku Malaysia Berhad (ITBM), 2013)
Halal: All that You Need To Know is a collection of articles covering a diverse range Halal lifestyle from food to cosmetics, tourism to logistics and finance to pharmaceutics. Halal is defined as permissible by the Islamic law. It exists in many aspects of life and comes with its counterpart toyyebah (pure and clean).